Molecular cloning, expression and functional analysis of foxl2 from Chinese sturgeon (Acipenser sinensis) in relation to sex differentiation - Hu, Yacheng; Tan, Ruihua; Li, Yang; Shu, Tingting; Yang, Gang; Chu, Zhong; Wang, Haoran; Liu, Xueqing; Zhu, Xin; Wang, Binzhong; Guo, Baifu; Wang, Runqiu; et al. (Frontiers in Marine Science, 2024)
Our knowledge of the regulatory mechanisms underlying the development of sexual characteristics in sturgeon is currently limited. Foxl2, a constituent of the forkhead/HNF-3-related transcription factor clan, offers precise gene regulation within specific tissues. It is identified for its ability to control ovarian aromatase, a key player in the processes of ovarian development and maturation. The purpose of this investigation was to study the sexually dimorphic manifestation of foxl2 in Chinese sturgeon during the stages of molecular and morphological sex differentiation.We successfully separated the full-length cDNAs of foxl2 in Chinese sturgeon. We detected a foxl2 gene in Chinese sturgeon and probed the expression profiles of this gene in a variety of somatic tissues in both female and male specimens. Foxl2 was predominantly expressed in the ovulatory organs of two-year-old Chinese sturgeon, with its presence considerably less in other somatic tissues. Foxl2 expression exhibited sexual dimorphism in gonads that had achieved morphological differentiation. We propose that the manifestation of foxl2 is intricately associated with the process of ovarian differentiation. Moreover, we posit that the mRNA quantities of foxl2 could serve as an accurate indicator for sex determination in sturgeon during their early growth stages.